Silane anchoring agent as well as preparation method and application thereof
By using epoxy group-containing alkoxysilane monomers for hydrolyzing and polycondensing with alkenyl group-containing acyloxysilanes, the existing small molecule structure and preparation of silane anchors are solved. Complex problems achieve efficient anchoring and environmentally friendly processes.
Patent Information
- Application Number
- CN202411597543.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-11
AI Technical Summary
The existing silane anchoring agents have small molecular structures during use, resulting in too many methoxy groups not involved in the reaction in the system, releasing a large amount of methanol, which is unfriendly to the environment, and the preparation process is complicated.
Hydrolytic polycondensation reaction with an epoxy group-containing alkoxy silane monomer and an alcohol aqueous solution under the action of a weak acid catalyst to obtain an epoxy group-containing silane oligomer, and then co-polycondensation reaction with an acyloxy silane containing alkenyl group-containing acyloxy silane. , silane anchoring agent is prepared.
It improves the interaction between silane anchoring agent and substrate, enhances its anchoring effect, meets the application needs of pressure-sensitive adhesives and release agents, and simplifies the preparation process, improves the utilization rate of raw materials, and is environmentally friendly.
Smart Images

Figure CN119431795A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of anchoring agents, and in particular relates to a silane anchoring agent and a preparation method and application thereof. Background Art
[0002] Silane anchoring agents are mainly used in silicone pressure-sensitive adhesives and release agents to improve the adhesion of the coating to the substrate, enhance the adhesion of the coating, and protect the adhesive layer from being contaminated or sticking to other objects and becoming ineffective.
[0003] Chinese patent CN105295414A discloses a method for preparing an anchoring agent, wherein γ-(2,3-epoxypropoxy)propyltrimethylolsilane or γ-(2,3-epoxypropoxy)propyltrimethoxysilane, vinyltriacetoxysilane, and ionic resin are prepared according to a certain ratio to obtain an anchoring agent.
[0004] Chinese patent CN106916309A discloses an addition type tackifier for silicone pressure-sensitive adhesive. The method comprises adding γ-(2,3-epoxypropoxy)propyltrimethoxysilane, vinyltriacetoxysilane and anhydrous aluminum chloride into a reaction kettle in proportion, reacting the mixture, vacuumizing the reaction kettle and collecting the product.
[0005] The silane anchoring agents obtained by the above two methods are mostly small molecular structures. Since there are a large number of methoxy groups that do not participate in the reaction in the system, a large amount of methanol is released during use, which is not environmentally friendly.
[0006] Chinese patent CN114196021A discloses an anchoring agent and its preparation method and application. The method is to prepare the anchoring agent by using a hydroxy-terminated polysiloxane containing a vinyl functional group and an organic siloxane monomer, a lithium catalyst, and an organic solvent.
[0007] The method adopted in this patent is that the first step of hydrolysis uses an alkaline catalyst. After the reaction is completed, it is necessary to obtain terminal hydroxyl polysiloxane by neutralization, dehydration, drying and filtration. The second step also requires the use of a lithium catalyst, which also requires neutralization, dehydration, drying and filtration. The whole reaction process is relatively complicated. Summary of the invention
[0008] In view of the above problems existing in the prior art, the present invention provides a silane anchoring agent and a preparation method thereof. The silane anchoring agent has good compatibility with the organosilicon system of the pressure-sensitive adhesive and the release agent; on the other hand, it has a strong interaction with the substrate, which improves the bonding effect of the organosilicon system on the substrate; that is, the silane anchoring agent can play a good anchoring role in the pressure-sensitive adhesive and the release agent, meeting the application requirements of the pressure-sensitive adhesive and the release agent. At the same time, the preparation process of the present invention has high raw material utilization rate, simple process and environmental protection.
[0009] To achieve the above object, the present invention adopts the following technical solutions:
[0010] A silane anchoring agent, the structural formula of which is shown in the following formula I:
[0011]
[0012] Where n is an integer, 1≤n≤10;
[0013] R1 represents methyl, hydroxy, methoxy or ethoxy;
[0014] R2 represents hydrogen, methyl or ethyl;
[0015] R3 represents γ-(2,3-epoxypropyloxy)propyl or β-(3,4-epoxycyclohexyl)ethyl;
[0016] R4 represents hydrogen, methyl, acetoxy or
[0017] R5 represents vinyl, allyl or butyl.
[0018] Preferably, the structural formula of the silane anchoring agent is as shown in Formula II below:
[0019]
[0020] Wherein, Ra represents a hydroxyl group or a methoxy group; R3 is the same as in formula I; and 2≤n≤5.
[0021] The present invention also provides a method for preparing the above-mentioned silane anchoring agent, comprising the following steps:
[0022] (S1) mixing an epoxy-containing alkoxysilane monomer with an alcohol aqueous solution, and subjecting the mixture to a hydrolysis and polycondensation reaction under the action of a weak acid catalyst to obtain an epoxy-containing silane oligomer; the molar ratio of the epoxy-containing alkoxysilane monomer to water in the alcohol aqueous solution is 1:(0.3-1.0);
[0023] (S2) A silane oligomer containing an epoxy group is subjected to a co-condensation reaction with an acyloxysilane containing an alkenyl group, and then low boiling points are removed and filtered to obtain a silane anchoring agent.
[0024] Furthermore, in step (S1), the molar ratio of the epoxy-containing alkoxysilane monomer to water in the alcohol-water solution is 1:(0.3-0.7), preferably 1:(0.5-0.7). When the epoxy-containing alkoxysilane monomer is hydrolyzed, part of its alkoxy groups are hydrolyzed into silanol groups, and then the silanol groups condense to produce water. If the amount of water is too low, too little alkoxy groups are hydrolyzed, and it is difficult to condense into oligomers; if the amount of water is too high, too many silanol groups are formed by hydrolysis of alkoxy groups, and the branching degree of the formed oligomers is too large, affecting the anchoring effect of the final anchoring agent; therefore, the amount ratio of the epoxy-containing alkoxysilane monomer to water should be controlled within the above range to partially hydrolyze the alkoxy groups.
[0025] Furthermore, the amount of the weak acid catalyst is 0.3-1.2wt%, preferably 0.4-0.8wt% of the epoxy-containing alkoxysilane monomer. Compared with alkaline catalysts and lithium catalysts, weak acid catalysts can reduce the ring opening of epoxy groups and can be directly used as catalysts in step (S2) without treatment.
[0026] Further, in step (S1), the epoxy-containing alkoxysilane monomer is at least one of γ-(2,3-epoxypropyloxy)propyltrimethoxysilane, γ-(2,3-epoxypropyloxy)propyltriethoxysilane, γ-(2,3-epoxypropyloxy)propylmethyldimethoxysilane, γ-(2,3-epoxypropyloxy)propylmethyldiethoxysilane, β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, and β-(3,4-epoxycyclohexyl)ethyltriethoxysilane; preferably γ-(2,3-epoxypropyloxy)propyltrimethoxysilane, γ-(2,3-epoxypropyloxy)propylmethyldimethoxysilane or β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane.
[0027] Furthermore, in step (S1), the water content in the alcohol aqueous solution is 10-20 wt%, the alcohol is methanol or ethanol, and the water is deionized water. The purpose of adding alcohol is to promote better compatibility between the aqueous phase and the epoxy-containing alkoxysilane monomer.
[0028] Further, in step (S1), the weak acid catalyst is at least one of an inorganic weak acid, an organic weak acid, a weak acid cation exchange resin, and a strong acid and weak base salt, such as formic acid, acetic acid, ferric chloride, ferrous chloride, cupric chloride, and ammonium chloride; preferably acetic acid or a weak acid cation exchange resin.
[0029] Furthermore, in step (S1), the conditions of the hydrolysis and polycondensation reaction are: temperature 40-65° C., time 2-6 h.
[0030] Furthermore, the structural formula of the epoxy-containing silane oligomer prepared in step (S1) is shown in the following formula III:
[0031]
[0032] Wherein, n, R1, R2, and R3 are the same as those in Formula I.
[0033] Furthermore, in step (S2), the molar ratio of epoxy-containing silane oligomer (calculated as epoxy-containing alkoxysilane monomer) to alkenyl-containing acyloxysilane is 1:(0.3-1), preferably 1:(0.5-0.7). After the co-condensation to form the silane anchoring agent, the alkenyl group can participate in the addition reaction of the organosilicon system and firmly bond with the coating; the epoxy group interacts with the substrate and is tightly connected; a certain balance is achieved between the two to play a good anchoring role, so the ratio of epoxy-containing silane oligomer to alkenyl-containing acyloxysilane needs to be controlled within the above range.
[0034] Furthermore, in step (S2), the alkenyl-containing acyloxysilane is at least one of vinyl triacetoxysilane, vinyl methyl diacetoxysilane, allyl triacetoxysilane, and butyl triacetoxysilane; preferably vinyl triacetoxysilane and vinyl methyl diacetoxysilane.
[0035] Furthermore, in step (S2), the co-condensation conditions are: temperature 40-65° C., time 2-8 h.
[0036] The present invention also provides the use of the above silane anchoring agent in the field of pressure-sensitive adhesives and release agents; preferably, the silane anchoring agent accounts for 1 to 3% of the total mass of the pressure-sensitive adhesive or the release agent.
[0037] Compared with the prior art, the present invention has the following beneficial effects:
[0038] (1) The anchoring agent of the present invention is a silane polymer with a large number of epoxy groups in the side groups, which has a low branching and non-over-crosslinked structure, thereby being able to play a good anchoring role; at the same time, the high content of epoxy groups can interact with the substrate and tightly connect to further promote the improvement of the anchoring effect.
[0039] (2) In the present invention, the epoxy-containing alkoxysilane monomer is first hydrolyzed and polycondensed to hydrolyze part of the alkoxy groups into silanol groups, thereby reducing the content of alkoxy groups in the system. When used in a pressure-sensitive adhesive or a release agent, its bonding performance with the substrate can be improved.
[0040] (3) The anchoring agent of the present invention is a polymer formed by the condensation of an epoxy-containing silane oligomer and an alkenyl-containing acyloxysilane. Different from physical blending, the epoxy group and the alkenyl group are both in the molecular chain of the polymer. Therefore, the silane anchoring agent of the present invention has good compatibility with the pressure-sensitive adhesive system and the release agent system; at the same time, it does not have the irritating odor problem existing in small molecule anchoring agents.
[0041] (4) In step (S1) of the present invention, silane oligomers are prepared by hydrolyzing and polycondensing epoxy-containing alkoxysilane monomers under the action of weakly acidic catalysts. Compared with alkaline catalysts and lithium catalysts, weakly acidic catalysts can not only reduce the ring-opening of epoxy groups, so that the epoxy content of the final anchoring agent is higher; but also can be directly applied to step (S2) without treatment and continue to be used as a catalyst; that is, the preparation process of the present invention has high raw material utilization and simple process. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 This is the H NMR spectrum of the silane anchoring agent prepared in Example 1.
[0043] Figure 2 This is the infrared spectrum of the silane anchoring agent prepared in Example 1. DETAILED DESCRIPTION
[0044] The present invention will be further described below in conjunction with specific embodiments, but the present invention is not limited to the following embodiments.
[0045] The experimental methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.
[0046] Example 1
[0047] A silane anchoring agent, the preparation method of which comprises the following steps:
[0048] (S1) 236 g (1 mol) of γ-(2,3-epoxypropoxy)propyltrimethoxysilane and 1.2 g of acetic acid were added to a reaction kettle, nitrogen protection was turned on, the temperature was raised to 50° C., and 36 g of an ethanol solution with a water content of 15 wt% (water was 5.4 g, i.e., 0.3 mol) was added dropwise under stirring for about 1 hour; after the addition was completed, the temperature was maintained for a hydrolysis and polycondensation reaction for 2 hours to obtain a mixed solution of epoxy-containing silane oligomers;
[0049] (S2) Add 162 g (0.7 mol) of vinyl triacetoxysilane to the above mixed solution, and carry out co-condensation reaction at 55° C. for 4 hours; after the reaction, perform pressure distillation to remove low-boiling substances in the system, and obtain a silane anchoring agent after filtering.
[0050] The NMR hydrogen spectrum of silane anchoring agent is as follows Figure 1 As shown, the infrared spectrum is Figure 2 shown.
[0051] The epoxy silane oligomer obtained in step (S1) was subjected to GPC test analysis, and the average degree of polymerization n was calculated to be 2.6.
[0052] Example 2
[0053] The rest is the same as Example 1, except that in step (S1), the amount of ethanol solution used is 90 g (water is 9 g, i.e., 0.5 mol).
[0054] The epoxy silane oligomer obtained in step (S1) was subjected to GPC test analysis, and the average degree of polymerization n was calculated to be 3.8.
[0055] Example 3
[0056] The rest is the same as Example 1, except that in step (S1), the amount of ethanol solution used is 84 g (water is 12.6 g, i.e., 0.7 mol).
[0057] The epoxy silane oligomer obtained in step (S1) was subjected to GPC test analysis, and the average degree of polymerization n was calculated to be 4.6.
[0058] Example 4
[0059] The rest is the same as Example 1, except that in step (S1), the amount of ethanol solution used is 120 g (water is 18 g, i.e., 1 mol).
[0060] The epoxy silane oligomer obtained in step (S1) was subjected to GPC test analysis, and the average degree of polymerization n was calculated to be 6.1.
[0061] Example 5
[0062] The rest is the same as Example 1, except that in step (S2), the amount of vinyltriacetoxysilane used is 6936 g (0.3 mol).
[0063] Example 6
[0064] The rest is the same as Example 1, except that in step (S2), the amount of vinyltriacetoxysilane used is 116 g (0.5 mol).
[0065] Example 7
[0066] The rest is the same as Example 1, except that in step (S2), the amount of vinyltriacetoxysilane used is 232 g (1 mol).
[0067] Example 8
[0068] The rest is the same as Example 1, except that: in step (S1), γ-(2,3-epoxypropyloxy)propyltrimethoxysilane is replaced by an equal molar amount of β-(3,4-epoxycyclohexyl)ethyltriethoxysilane; in step (S2), vinyldimethylacetoxysilane vinyltriacetoxysilane is used, and the co-condensation time is 6 hours.
[0069] Comparative Example 1
[0070] The rest is the same as Example 1, except that in step (S1), the amount of ethanol solution used is 360 g (water is 54 g, i.e., 3 mol).
[0071] Comparative Example 2
[0072] The rest is the same as Example 1, except that in step (S1), the amount of ethanol solution used is 12 g (water is 1.8 g, i.e., 0.1 mol).
[0073] Comparative Example 3
[0074] The rest is the same as Example 1, except that in step (S1), an equal mass of magnesium oxide is used to replace acetic acid.
[0075] Results and Analysis
[0076] (1) Structural analysis
[0077] Figure 1 This is the H NMR spectrum of the silane anchoring agent prepared in Example 1. The chemical shifts in the figure show the hydrogens connected to each group. Figure 1 As indicated by the markings.
[0078] Figure 2 This is the infrared spectrum of the silane anchoring agent prepared in Example 1. The characteristic peaks of the main functional groups are marked as shown in the figure.
[0079] Based on the NMR spectrum and infrared spectrum, it can be concluded that the structural formula of the silane anchoring agent prepared in Example 1 is:
[0080]
[0081] Ra represents a hydroxyl group or a methoxy group.
[0082] (2) Performance testing
[0083] The silane anchoring agents prepared in the embodiment and the test example were respectively prepared according to the pressure-sensitive adhesive formula in Table 1 below, coated on the corona-treated PET film using a 50-wire coating rod, baked at 150° C. for 5 minutes, and then the samples were tested as follows:
[0084] Anchorage: The anchorage is determined by rubbing the steel bars with the 100-grid method to see if there is any debonding. The grade is 1-5, with grade 3 as qualified, grades below 3 as unqualified, grade 4 as good, and grade 5 as excellent. The anchorage is tested by boiling in water at 100°C for 2 hours and in a double 85 environment (temperature 85°C, humidity 85%) for 1 week.
[0085] Adhesion: According to ASTM D3330, the AR2000 adhesion / peel tester of Cheminstruments, USA, was used to measure the high temperature initial adhesion (70°C, 20 min) and high temperature and high humidity aging adhesion (70°C, humidity 80%, placed for 3 days).
[0086] The test results are shown in Table 2.
[0087] Table 1 Pressure sensitive adhesive formulation
[0088] Components Mass Vinyl Silicone Rubber 100 MQ methyl silicone resin 92 Hydrogen silicone oil 5 Custer Catalyst 1 Silane anchoring agent 4 Toluene 80
[0089] Table 2 Silane anchoring agent performance test
[0090]
[0091] It can be seen from Table 2 that the anchoring agent prepared by the present invention has a good effect in application and effectively improves the bonding performance of the pressure-sensitive adhesive. It has excellent anchoring properties both in 100°C boiling water and in a double high temperature and high humidity environment; when applied to a pressure-sensitive adhesive system, the adhesion fluctuation is small under high temperature and high humidity conditions.
[0092] The above contents are only preferred embodiments of the present invention and are not intended to limit the implementation scheme of the present invention. A person skilled in the art can easily make corresponding changes or modifications based on the main concept and spirit of the present invention. Therefore, the protection scope of the present invention shall be based on the protection scope required by the claims.
Claims
1. A silane anchoring agent, characterized in that: Its structural formula is shown in the following formula I: Where n is an integer, 1≤n≤10; R1 represents methyl, hydroxy, methoxy or ethoxy; R2 represents hydrogen, methyl or ethyl; R3 represents γ-(2,3-epoxypropyloxy)propyl or β-(3,4-epoxycyclohexyl)ethyl; R4 represents hydrogen, methyl, acetoxy or R5 represents vinyl, allyl or butyl.
2. The silane anchoring agent according to claim 1, characterized in that Its structural formula is shown in the following formula II: Wherein, Ra represents a hydroxyl group or a methoxy group; R3 is the same as in formula I; and 2≤n≤5.
3. The method for preparing the silane anchoring agent according to claim 1 or 2, characterized in that: The following steps are involved: (S1) mixing an epoxy-containing alkoxysilane monomer with an alcohol aqueous solution, and subjecting the mixture to a hydrolysis and polycondensation reaction under the action of a weak acid catalyst to obtain an epoxy-containing silane oligomer; the molar ratio of the epoxy-containing alkoxysilane monomer to water in the alcohol aqueous solution is 1:(0.3-1.0); (S2) A silane oligomer containing an epoxy group is subjected to a co-condensation reaction with an acyloxysilane containing an alkenyl group, and then low boiling points are removed and filtered to obtain a silane anchoring agent.
4. The preparation method according to claim 3, characterized in that: In step (S1), the molar ratio of the epoxy-containing alkoxysilane monomer to water in the alcohol aqueous solution is 1:(0.3-0.7), preferably 1:(0.5-0.7); the amount of the weak acid catalyst is 0.3-1.2wt% of the epoxy-containing alkoxysilane monomer.
5. The preparation method according to claim 3, characterized in that: In step (S1), the epoxy-containing alkoxysilane monomer is at least one of γ-(2,3-epoxypropoxy)propyltrimethoxysilane, γ-(2,3-epoxypropoxy)propyltriethoxysilane, γ-(2,3-epoxypropoxy)propylmethyldimethoxysilane, γ-(2,3-epoxypropoxy)propylmethyldiethoxysilane, β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, and β-(3,4-epoxycyclohexyl)ethyltriethoxysilane; preferably γ-(2,3-epoxypropoxy)propyltrimethoxysilane, γ-(2,3-epoxypropoxy)propylmethyldimethoxysilane or β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane.
6. The preparation method according to claim 3, characterized in that: In step (S1), the water content in the alcohol aqueous solution is 10-20 wt%, the alcohol is methanol or ethanol, and the water is deionized water; and / or The weak acid catalyst is at least one of an inorganic weak acid, an organic weak acid, a weak acid cation exchange resin, and a strong acid weak base salt; and / or The conditions of the hydrolysis and polycondensation reaction are: temperature 40-65° C., time 2-6 hours.
7. The preparation method according to claim 3, characterized in that: The structure of the epoxy-containing silane oligomer prepared in step (S1) is shown in the following formula III: Wherein, n, R1, R2, and R3 are the same as those in Formula I.
8. The preparation method according to claim 3, characterized in that: In step (S2), the molar ratio of epoxy-containing silane oligomer (calculated as epoxy-containing alkoxysilane monomer) to alkenyl-containing acyloxysilane is 1:(0.3-1), preferably 1:(0.5-0.7); the alkenyl-containing acyloxysilane is at least one of vinyl triacetoxysilane, vinyl methyl diacetoxysilane, allyl triacetoxysilane, and butyl triacetoxysilane; preferably vinyl triacetoxysilane and vinyl methyl diacetoxysilane.
9. The preparation method according to claim 3, characterized in that: In step (S2), the co-condensation conditions are: temperature 40-65° C., time 2-8 h.
10. Use of the silane anchoring agent according to claim 1 or 2 in the field of pressure-sensitive adhesives and release agents; preferably, the silane anchoring agent accounts for 1 to 3% of the total mass of the pressure-sensitive adhesive or the release agent.
Citation Information
Patent Citations
Tackifier for LED packaging adhesive and preparation method of tackifier
CN104877139A
Anchoring agent
CN105295414A
Addition type organic silicon pressure-sensitive adhesive tackifier
CN106916309A
Anchoring agent and preparation method and application thereof
CN114163645A
Anchorage additive emulsion for silicone release coating composition
US20160376475A1